2022
DOI: 10.3389/fimmu.2022.1027403
|View full text |Cite
|
Sign up to set email alerts
|

The emerging role of histone deacetylase 1 in allergic diseases

Abstract: Histone deacetylase 1 (HDAC1) is a unique member of the classes I HDACs and helps to regulate acute and chronic adaptation to environmental stimuli such as allergen, stress. Allergic diseases are complex diseases resulting from the effect of multiple genetic and interacting foreign substances. Epigenetics play an important role in both pathological and immunomodulatory conditions of allergic diseases. To be consistent with this role, recent evidence strongly suggests that histone deacetylase 1 (HDAC1) plays a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 93 publications
1
7
0
Order By: Relevance
“…Histone deacetylase 1 (HDAC1) is a member of class I HDACs, and plays an important role in adapting to external stimuli, including stress and allergens [39]. Given that Th2 cells are a major cause of allergic disorders, we anticipated that HDACs would play a part in controlling the synthesis of IL-4 and IL-13.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Histone deacetylase 1 (HDAC1) is a member of class I HDACs, and plays an important role in adapting to external stimuli, including stress and allergens [39]. Given that Th2 cells are a major cause of allergic disorders, we anticipated that HDACs would play a part in controlling the synthesis of IL-4 and IL-13.…”
Section: Resultsmentioning
confidence: 99%
“…Inhibition of HDACs resulted in an up-regulated IL-13 production, while the presence of calcitriol affected the recruitment of HDAC1 in Th2 cells. Histone deacetylase 1 (HDAC1) is a member of class I HDACs, and plays an important role in adapting to external stimuli, including stress and allergens [39]. Given that Th2 cells are a major cause of allergic disorders, we anticipated that HDACs would play a part in controlling the synthesis of IL-4 and IL-13.…”
Section: Name Of the Primersmentioning
confidence: 99%
“…Of this protein bunch, of significant interest is histone deacetylase (HDAC 1), which was present in the samples from D16 until parturition (M5). This protein might contribute to stress alleviation since it is involved in cell differentiation both in the embryo and maternal organism and in signal transduction specifically related to immune response and histone H3 and H4 deacetylation [47,48]. Studies have proven that a reduction in HDAC 1 concentration is directly linked to abnormalities caused by stress in early life [48].…”
Section: Discussionmentioning
confidence: 99%
“…MDM2 E3 ligase mediates ubiquitination and degradation of HDAC1 in vascular calcification 45 . Although HDAC1 plays a vital role in Th cell function and differentiation 14 , its regulation through ubiquitination in CD4 + T cells remains to be clarified. In this study, we found that RNF157 is a key ubiquitination regulator of HDAC1.…”
Section: Discussionmentioning
confidence: 99%